PEMAKAIAN JENIS BH (BREAST HOLDER) MEMPENGARUHI NYERI PUNGGUNG PADA IBU HAMIL DI POLI BKIA RUMAH SAKIT ISLAM SURABAYA - Garini, Elanda Pebianita; Afiyah, R. Khairiyatul (Jurnal Ilmiah Kesehatan, 2014)
Back pain in pregnant women can disturb her daily activities, therfore she needs much more lying. Wearing a proper BH will help reducing a strain on the back. The purpose of this study is to determine the relationship using of the type of BH (Breast Holder) with back pain in pregnant women in Children and Maternity Department of Islamic Hospital Surabaya.  Study design is analytic with cross sectional approach. Population were all pregnant women in trimester II and III by 52 person, the samples were 46 respondents taken by simple random sampling technique. Independent variables is using the types of BH (Breast Holder), the dependent variable is back pain. It?s instruments are observation and interviews, data then analyzed by Chi-Square test with significance level ? = 0.05 when ? <? so Ho is rejected it means there is a connection using the type of BH (Breast Holder) with back pain. The most part (67.4%) of respondents uses the reguler BH and the most part (65.2%) of respondents do have back pain. Chi-square test results obtained ? = 0.000 <? = (0.05) Ho rejected, means there is a relationship the use of the type BH (Breast Holder) with back pain.  Wearing BH (Breast Holder) gives influence in back pain. Maternity bra can reduce back pain during pregnancy. Hopefully the nurse spreads the educational information about the importance of wearing maternity bra to pregnant women.